Advancing Equitable Access to Medicines in Southeast Asia: A Comprehensive Policy Analysis of the 2025 Regional Position Paper - Mayadhar Sethy* (CV. Proaksara Global Transeduka, 2026)
The Southeast Asia region faces persistent challenges in ensuring equitable access to affordable, quality medicines despite decades of economic growth and health system advancements. This article provides a comprehensive policy analysis of the